Liquid-phase hydrogenation of unsaturated aldehydes: enhancing selectivity of multiwalled carbon nanotube- supported catalysts by thermal activation - Machado, Bruno (2011)
Platinum and iridium organometallic precursors are used to prepare nanosized, thermally stable multiwalled carbon nanotube- supported catalysts. The materials are characterized by N2 adsorption at 77 K, temperature-programmed desorption coupled with mass spectrometry, H2 chemisorption, transmission electron microscopy and thermogravimetric analysis; they are tested in the selective hydrogenation of cinnamaldehyde to cinnamyl alcohol under mild conditions (363 K and 1 MPa). A thermal activation at 973 K is found to have a very positive effect over both activity and selectivity, leading to selectivities of approximately 70%, at 50% conversion, regardless of the active metal phase (Pt or Ir). Since no noticeable differences in the metal particle sizes are detected, the results are interpreted in light of an enhanced metal/support interaction. This effect, induced by the removal of oxygenated surface groups, is thought to change the adsorption mechanism of the cinnamaldehyde molecule.